Pelestarian Manuskrip Kuno Melayu Nusantara Perspektif Industries - Nofrizal, Nofrizal (AL-ADYAN, 2020)
The ancient manuscript is one of Indonesia’s valuable cultural heritage. One of the primary sources of research, that presence is certainly worthy of appreciation because it also contributes to the development of the scientific realm. Research that utilizes ancient manuscripts as objects of study, has been carried out by many foreign and native scholars lately. But in reality, this ancient manuscript could not be accessed easily. This happened because these ancient manuscripts were not mas-produced and distributed, and there were minimal conservation efforts. Therefore the concern of the government of the nation’s assets is questionable. This paper confirms that efforts to preserve  archipelago ancient manuscripts by Pustaka Nasional Republik Indonesia (PNRI) as representatives of the government, seem to be very slow and inefficient. Their conversation efforts appear to be more reactionary than visionary. So much of the knowledge contained in the archipelago from ancient manuscripts is lost together with the destruction of the ancient manuscripts themselves. The solution must be sought immediately, so that future generations can also enjoy the nation’s cultural heritage.